Can Web 2.0 be Used Effectively Inside Organisations? - Sağsan, Mustafa (Information World, 2007)
There is a common conception amongst higher and middle management that facilities that are “good for the Internet” can be transferred for application to the enterprise intranet. The latest fashion to arrive on the information scene is the Web 2.0 phenomenon, a range of tools including blogs, Wikis and RSS. This paper presents a brief overview of the Web 2.0 phenomenon and some tentative views on the relationship between Web 2.0 tools and the more formal and traditional tools used in information handling. The paper concludes that whereas Web 2.0 facilities will grow and develop on the Internet, the use of Web 2.0 facilities within the enterprise should be carefully planned as adjuncts to existing facilities, not as substitutes.
Keywords: Opinion Papers